2019
DOI: 10.1007/s40261-019-00869-3
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab Versus Docetaxel for Previously Treated Advanced Non-Small Cell Lung Cancer in China: A Cost-Effectiveness Analysis

Abstract: Background and Objective The economic assessment of immuno-oncology agents in Chinese patients is limited despite a need for new therapies. Nivolumab is the first immune checkpoint inhibitor approved for the second-line treatment of nonsmall cell lung cancer (NSCLC) in China, and it significantly prolongs overall survival. However, considering the high cost of nivolumab, it is urgent to assess its value in China in terms of both efficacy and cost. The objective of this study was to investigate the cost-effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 29 publications
(37 reference statements)
2
46
1
Order By: Relevance
“…The characteristics of all included studies are presented in S1 Table. Most of the studies were conducted in 2019 [28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Studies were conducted from countries all over the world, with ten from the USA [22-27, 29, 30, 32, 33], seven from China (one from HongKong) [34][35][36][38][39][40][41], two from Canada [20,37], and one each from Australia [31], France [28] and Switzerland [21]. Most studies were assessed from the perspective of health care system (N = 12) [20-22, 25, 26, 28-31, 35, 37, 40], some used a payer perspective (N = 8) [23,24,27,32,33,38,39,41], and the remainder used a perspective of society (N = 1) [34] and hospital authority (N = 1) [36].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of all included studies are presented in S1 Table. Most of the studies were conducted in 2019 [28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Studies were conducted from countries all over the world, with ten from the USA [22-27, 29, 30, 32, 33], seven from China (one from HongKong) [34][35][36][38][39][40][41], two from Canada [20,37], and one each from Australia [31], France [28] and Switzerland [21]. Most studies were assessed from the perspective of health care system (N = 12) [20-22, 25, 26, 28-31, 35, 37, 40], some used a payer perspective (N = 8) [23,24,27,32,33,38,39,41], and the remainder used a perspective of society (N = 1) [34] and hospital authority (N = 1) [36].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Subsequently, plenty of economic studies around the world also evaluated the cost-effectiveness of second-line therapies for patients with recurrent NSCLC. Three studies, one each from Switzerland, US and China, showed that nivolumab is not cost-effective compared with docetaxel for patients with previously treated advanced NSCLC [21,31,35]. Huang et al [24] found that pembrolizumab is cost-effective versus docetaxel in pre-treated advanced NSCLC patients with PD-L1 � 50% from the US third-party payer perspective.…”
Section: Plos Onementioning
confidence: 99%
“…Four studies were conducted in China, and one of them was conducted in the Hong Kong region. Fourteen, 21,22,[24][25][26][27][28][29][30][31]34,[38][39][40] four, 33,[35][36][37] and three 12,23,32 studies focused on pembrolizumab, nivolumab, and atezolizumab, respectively. No study investigated durvalumab.…”
Section: General Characteristicsmentioning
confidence: 99%
“…Most of them reported the results in terms of cost per quality-adjusted life years (QALYs) and cost per life year (LY) gained. Among these studies, 16 12,21-31,34,38-40 and 5 32,33,[35][36][37] were about firstand second-line treatments for NSCLC, respectively. One study 12 had two base cases.…”
Section: General Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation